2011
DOI: 10.1007/978-3-642-21470-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Operation Based Model Representation: Experiences on Inconsistency Detection

Abstract: International audienceKeeping the consistency between design models is paramount in complex contexts. It turns out that the underlying Model Representation Strategy has an impact on the inconsistency detection activity. The Operation Based strategy represents models as the sequence of atomic editing actions that lead to its current state. Claims have been made about gains in time and space complexity and in versatility by using this kind of representation when compared to the traditional object based one. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…With the increasing complexity and size of industrial design models, we believe that optimal memory management (scalability) in inconsistency management is as important as response time (efficiency). This is also confirmed by our industrial partners, which have realized a case study that confirms the critical need for more optimal memory management for large and complex models .…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…With the increasing complexity and size of industrial design models, we believe that optimal memory management (scalability) in inconsistency management is as important as response time (efficiency). This is also confirmed by our industrial partners, which have realized a case study that confirms the critical need for more optimal memory management for large and complex models .…”
Section: Introductionsupporting
confidence: 73%
“…Second, it presents a case study that has been performed by Thales, our industrial partner as a part of the MOVIDA project. Thales wanted to try Praxis on their domain specific models, on the basis of Eclipse Modeling Framework .…”
Section: Beyond Java: Two Praxis Case Studiesmentioning
confidence: 99%
“…The existing approaches typically compute a set of repairs for each of the detected inconsistencies. Studies reported on the adoption of inconsistency detection and repair in various industries, such as by Thales a company in aeronautic, transport, and security [42], and Van Hoecke Automation a company in the areas of production automation and processing [12]. In this paper, we argue that merely proposing repairs is not yet sufficient, and consequences of repairs must be handled too.…”
Section: Introductionmentioning
confidence: 88%
“…Operation-based model representation [32] has been proposed for reasoning about streams of model operations. The C-Praxis approach [35] defines six CRUD model operations and defines how these operations interact.…”
Section: Conflict-free Replicated Data Typesmentioning
confidence: 99%